DAMPAK CURRENT RATIO DAN RETURN ON EQUITY TERHADAP TRADING VOLUME ACTIVITY DENGAN PRICE TO BOOK VALUE SEBAGAI VARIABEL MODERATING PADA JAKARTA ISLAMIC INDEX PERIODE 2015 – 2019 - Susanti, Elly (Universitas Djuanda, 2020)
Investors always believe that if the company performs well it can increase the volume of stock trading. Therefore, many companies are trying to increase company activity and optimize all company resources in order to increase trading volume activity. This study examines and analyzes the effect of Current Ratio, Return On Equity on Trading Volume Activity with Price To Book Value, which is a moderating variable in the Jakarta Islamic Index for the 2015 - 2019 period on the IDX. To obtain data, the website www.idx.co.id is used as secondary data. The population is 50 issuers and the sample technique uses purposive sampling, thus the sample is 10 issuers. Furthermore, the application used in analyzing quantitative data is SPSS version 21.With the results obtained, Current Ratio and Return On Equity have a significant effect on Trading Volume Activity, but Price to Book Value is not able to be a moderating variable between Current Ratio and Return On Equity to Trading. Activity Volume.